Pelatihan pemanfaatan limbah sabut kelapa sebagai media tanam anggrek bagi pelajar sekolah menengah atas di Kabupaten Manokwari: Training on the utilization of coconut shell waste as a growing media for orchids for high school students in Manokwari Regency - Agustina Y. S. Arobaya; Meliza S. Worabai; Matheus Beljai (Fakultas Peternakan Universitas Papua, 2022)
ABSTRACT The ex-school program was conducted as early as possible to the pupils and students from many levels of education from kinder garden to the high schools. One of the ex-school activities conducted by study program of diploma in the Faculty of Forestry at University Papua is an extension program on how to use the disposal materials from coconut fiber to create an environmentally friendly pot to grow orchid plants. Method employs in this activity is tutorials and a direct practice that took place in the classroom of the Faculty of Forestry. Participants come from three high schools in Manokwari Regency i.e. SMU Oikumene, SMU Anu Beta Tuba and SMK 3 Conservation Department. Each school sent their 20 students as a representative from their schools. Results from this activity is pots in many size (small, medium and large) and planting orchid on the pot. Orchid plants are collected by academic member during the fieldwork in many areas in Papua and are deposite in the screen house of Fahutan Unipa. Keywords: Capacity-building; Coco-fiber; Extention-program; High school students; Orchids ABSTRAK Program ekstra kurikuler dilaksanakan sejak dini pada berbagai tingkatan pendidikan mulai dari kelompok bermain hingga sekolah menengah atas. Salah satu aktivitas ko-kurikuler yang dilakukan oleh Prodi D3 KSH Fakultas Kehutanan Universitas Papua terhadap siswa-siswa SMU di Kabupaten Manokwari adalah dengan melakukan kegiatan pelatihan pemanfaatan limbah sabut kelapa untuk diolah menjadi produk ekonomi kreatif yang dapat dikembangkan oleh siswa SMU di sekolah mereka sebagai media tanam ramah lingkungan dan ekonomis. Metode pendekatan yang dilakukan dalam kegiatan ektra kurikuler adalah dengan ceramah dan praktek kerja langsung pada saat berlangsungnya kegiatan di Fakultas Kehutanan Universitas Papua. Peserta berasal dari SMU Oikumene, SMU Anu Beta Tuba, dan SMK 3 Jurusan Konservasi di Kabupaten Manokwari. Hasil dari pelatihan berupa pot media tanam dengan berbagai ukuran (kecil, sedang dan besar) dan penanam langsung spesies anggrek yang sudah dikoleksi oleh staf dosen di Fakultas Kehutanan Unipa. Kata kunci: Anggrek; Media serabut kelapa; Pelajar SLTA; Pemberdayaan masyarakat; Program pelatihan